Institutional Conditions for Strengthening the Position of Organic Farming as a Component of Sustainable Development - Łuczka, Władysława (Problemy Ekorozwoju, 2021)
In recent years, the development of organic farming has slowed down, especially in the European Union. This is a factor of importance for sustainable development prospects of the agricultural sector. Although the European Union places more and more emphasis on environmental goals set under the Common Agricultural Policy, two-thirds of the agricultural budget in the 2014-2020 financial perspective are allocated to support conventional farming. In 2014-2018, some member countries witnessed stagnation or decline in the area of organic farmland. This means that in the context of market imperfections – and in the absence of valuation of public goods – microeconomic costs incurred by organic farmers continue to exceed the benefits they reap. The level of support must be high enough to stimulate the development of organic farming in the long run. Therefore, it is recommended that the future support mechanism provide financial encouragement for organic farming, revise the principles for granting payments, tighten the system, and minimize the amount of payments decoupled from production volumes.